Legal Analysis of Code of Conduct and Joint Development Agreement In the South China Sea - Febrianingsih, Nurvairah Dwi; Adel Zain Filadelfia (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
The South China Sea territorial conflict emerged following the People’s Republic of China’s (PRC) claim over the Ten-Dash Line, which overlaps with the maritime entitlements of several coastal states, including the Philippines, Vietnam, Malaysia, Brunei Darussalam, and Indonesia’s Exclusive Economic Zone in the Natuna area. China bases its claim on historical grounds, a position strongly contested, particularly by the Philippines through arbitration before the Permanent Court of Arbitration in 2013. Despite the arbitral award, the dispute remains unresolved and continues to generate legal and political tensions. This study employs a normative legal research method to examine the legal implications of the Code of Conduct (CoC) and the Joint Development Agreement (JDA) in managing the South China Sea dispute under international law. The analysis is conducted through examination of international legal norms, principles, and relevant instruments, particularly the 1982 United Nations Convention on the Law of the Sea (UNCLOS). The study finds that neither the CoC nor the JDA constitutes a legally binding dispute settlement mechanism. Instead, both function primarily as conflict management instruments aimed at preventing escalation and facilitating cooperation. Consequently, reliance on these mechanisms alone is insufficient to ensure certainty or resolve sovereignty disputes.